The effect of crystallite size on pressure amplification in switchable porous solids - Krause, Simon; Bon, Volodymyr; Senkovska, Irena; Toebbens, Daniel M.; Wallacher, Dirk; Pillai, Renjith S.; Maurin, Guillaume; Kaskel, Stefan (Nature Communications, 2018)
Negative gas adsorption (NGA) in ordered mesoporous solids is associated with giant contractive structural transitions traversing through metastable states. Here, by systematically downsizing the crystal dimensions of a mesoporous MOF (DUT-49) from several micrometers to less than 200 nm, counterintuitive NGA phenomena are demonstrated to critically depend on the primary crystallite size. Adsorbing probe molecules, such as n-butane or nitrogen, gives insights into size-dependent activation barriers and thermodynamics associated with guest-induced network contraction. Below a critical crystal size, the nitrogen adsorption-induced breathing is completely suppressed as detected using parallelized synchrotron X-ray diffraction-Adsorption instrumentation. In contrast, even the smallest particles show NGA in the presence of n-butane, however, associated with a significantly reduced pressure amplification. Consequently, the magnitude of NGA in terms of amount of gas expulsed and pressure amplification can be tuned, potentially paving the way towards innovative concepts for pressure amplification in micro-and macro-system engineering.
CRIS-Team Scopus Importer:2022-04-14